Personalized Nursing and Health Care - Suhonen Riitta; Stolt Minna; Edvardsson David (MDPI, 2026)
This Special Issue of the Journal of Personalised Medicine invited manuscripts that further establish the current state of science relating to personalized nursing and health care. We welcomed manuscripts that highlight and further the knowledge base conceptually, instrumentally, observationally and experimentally, with sound theoretical and methodological underpinnings and implications for research, theory and clinical work in the disciplines of nursing, medicine, allied health and beyond. As there has been a rapid development in the
academic literature over the last ten years in terms of papers relating to individualization, personalization, patient-, client-, consumer- and person-centredness, with work on conceptual, instrumental, observational and experimental levels, this theme seemed timely and relevant.